Effects of Enriched Housing Design on Broiler Performance, Welfare, Chicken Meat Composition and Serum Cholesterol - Simsek, Ulku Gulcihan; Dalkilic, Bestami; Ciftci, Mehmet; Cerci, Ibrahim Halil; Bahsi, Muammer (Veterinarni A Farmaceuticka Univerzita Brno, 2009)
This experiment was conducted to determine the effects of enrichment housing design on performance, selected welfare indicators, chicken meat composition and serum cholesterol concentration of broiler chicken. For this purpose, 480 Ross-308 chicks were assigned to two groups, Control and Test, each with 4 replications. The pens of the Test Group were enriched with perches and sand bedding. At the end of the study, 8 males and 8 females whose live weights were close to the group average from each group were slaughtered. Their blood was collected and serum was separated. For chemical analysis of the chicken meat, whole carcasses of 4 males and 4 females, and half of the breast and left thigh from the remaining 4 males and 4 females were collected. In the carcass group, whole carcass with its bones was minced, whereas in the other groups breast and tight meat were separated from the bones and minced in a meat grinder, homogenized with an electronic mixer, then flash frozen (-40 degrees C, 8-10 h) and stored (-20 degrees C, 3-4 weeks) until analysed. There was no significant difference between the groups in body weight, daily weight gain, feed intake, feed conversion and survivability. Litter moisture of the sand bedding was lower than that of the wood shavings. Contact dermatitis of hocks was reduced in the Test Group (P < 0.05). Length, width, bone mineral content (BMC) and bone mineral density (BMD) of the left tibiotarsus were similar between groups. The protein ratio of thigh meat was higher (P < 0.01), and fat ratio of the meat was lower (P < 0.05) in the Test Group. Enriched housing design increased serum HDL cholesterol level and decreased thigh meat cholesterol level (P < 0.05). In conclusion, it was found that housing enriched with perches and sand bedding in addition to wood shavings bedding improved broiler welfare and meat quality.
Keywords: Broiler chickens; environmental enrichment; housing design; performance; welfare; meat quality; serum cholesterol